Nature-derived Quinolines and Isoquinolines: A Medicinal Chemistry Perspective - Gupta, Mohit; Patel, Saloni (Current Traditional Medicine, 2021)
Quinoline and isoquinoline motifs are commonly encountered in natural products of diverse origins. These moderately basic fused-heterocyclic rings containing natural products are adorned with remarkable biological activities with clinical use in various diseases demonstrating nature elegance and creativity. Therefore, these privileged rings have attracted profound interest from the scientific community. In this perspective, we have discussed medicinal chemistry perspective of the natural products containing quinoline and isoquinoline scaffolds.
Keywords: natural products